Effect of adhesive type, application technique, and immediate dentin sealing on the shear bond strength of lithium disilicate - Seantiga, Viera; Untara, Tri Endra; Ratih, Diatri Nari (Majalah Kedokteran Gigi Indonesia, 2025)
Immediate dentin sealing (IDS) is a technique involving the application of adhesive material to freshly prepared dentin for indirect restorations. This method prevents contamination by saliva, debris, and bacteria from penetrating dentinal tubules, which could otherwise compromise the bonding strength of restorative materials. This study aimed to evaluate the effects of different adhesive types and application techniques in IDS on the shear bond strength (SBS) of lithium disilicate. The adhesive systems investigated included an eighth-generation adhesive and a universal adhesive, each applied using both total-etch and self-etch techniques. Twenty-eight upper premolars were divided into four groups, with buccal crown surfaces prepared for IDS treatment as follows: Group I – eighth-generation adhesive with total-etch; Group II – eighth-generation adhesive with self-etch; Group III – universal adhesive with total-etch; and Group IV – universal adhesive with self-etch. Lithium disilicate was cemented onto the dentin surfaces treated with IDS and then immersed in distilled water for 24 hours prior to SBS testing. The results showed that both adhesive type and application technique significantly influenced SBS (p < 0.05). No significant differences were observed among Groups II, III, and IV. However, Group I demonstrated the lowest SBS. In conclusion, the findings indicate that both the choice of adhesive and application technique in IDS significantly affect the shear bond strength of lithium disilicate.